Padronização do modelo de dismenorreia primária e a prevenção das alterações induzidas no sistema reprodutor feminino de ratas Wistar tratadas com Spirulina platensis - Lacerda Júnior, Francisco Fernandes (2022)
Primary dysmenorrhea (DisP) is the main cause of chronic pelvic pain that affects women and may be associated with genetic, social and behavioral factors. The pharmacotherapy of this disorder involves the use of non-steroidal anti-inflammatory drugs and antispasmodics, however, many women do not respond well to these treatments. Thus, aiming at new therapeutic alternatives for the prevention of DisP, the effect of supplementation with Spirulina platensis (SP), an algae with anti-inflammatory and antioxidant effects, for 8 weeks (v.o), in a DisP model, was evaluated. The experimental procedures were approved by the Ethics Committee on the Use of Animals of the UFPB (2240150621 and 1886010520). The animals were divided into the following groups: control (GC), DisP and groups treated with scopolamine + dipyrone (Esc + Dip) or ibuprofen (IBU) and groups supplemented with SP at doses of 50 (SP50) and 100 mg/kg ( SP100). For this, a model of DisP induced by the administration of diethylstilbestrol and oxytocin was standardized and promoted, in vivo, the increase in the writhing score in the rats, which was decreased by the standard drugs (Esc + Dip or IBU). Furthermore, in vitro, DisP increased the myometrial layer and promoted damage to the uterine endometrial layer, increased contractile reactivity and decreased relaxant in rat uterus and increased oxidative stress in rat uterus and ovaries. In view of these changes caused by DisP, SP supplementation promoted an antidysmenorrhea effect. The SP50 and SP100 groups in in vivo studies partially prevented the increase in uterine writhing, probably by promoting anti-inflammatory or antispasmodic effects, whereas in the in vitro parameters SP at both doses prevented the increase in the myometrial layer and damage to the uterine endometrial layer. , however, in the ovaries, the alga at both doses did not change the expression of the follicles, such effects could possibly be attributed to the inhibition of estrogenic effects. In the oxytocin-induced uterine contractile reactivity, only SP100 totally prevented the increase in potency and partially the maximum effect of oxytocin, suggesting that the alga may be decreasing the affinity of oxytocin to its receptor. When the contractile agent used was PGF2α, it was found that only SP100 partially prevented the increase in potency, thus suggesting that SP may be promoting negative effects on the affinity of PG to its receptor. Differently, in the electromechanical coupling of contraction against KCl, SP, at doses of 50 and 100 mg/kg, prevented the increase in potency, in relation to the prevention of the increase in maximum efficacy, SP was more effective at dose 100 than at dose 100. at 50 mg/kg, suggesting that SP may be down-regulating the opening/activation of Cav. In relaxation, we found that SP (50 mg/kg) prevented the decrease in the relaxing efficacy of isoprenaline and nifedipine. At a dose of 100 mg/kg, SP prevented the decrease in the potency and relaxing efficacy of isoprenaline and nifedipine, promoted by DisP, this set of results suggests that SP can positively modulate targets in the uterine adrenergic pathway and negatively the activation of Cav. In addition, SP (50 mg/kg) improved oxidative stress parameters by preventing the increase in MDA levels and the decrease in CAT in ovaries. In SP (100 mg/kg) it prevented the increase in MDA and decrease in CAT and in uterus and ovaries induced by DisP, suggesting that the alga may be reducing/neutralizing the formation of ROS. Therefore, supplementation with S. platensis prevents uterine hypercontractility, as well as increased oxidative stress in the uterus and ovaries of rats caused by DisP and appears as an alternative for the treatment of DisP.